Development of Steel Fiber-Reinforced Expanded-Shale Lightweight Concrete with High Freeze-Thaw Resistance. (2nd April 2018) - Zhao, Mingshuang; Zhang, Xiaoyan; Song, Wenhui; Li, Changyong; Zhao, Shunbo
Abstract : For the popularized structural application, steel fiber-reinforced expanded-shale lightweight concrete (SFRELC) with high freeze-thaw resistance was developed. The experimental study of this paper figured out the effects of air-entraining content, volume fraction of steel fibers, and fine aggregate type. Results showed that while the less change of mass loss rate was taken place for SFRELC after 300 freeze-thaw cycles, the relative dynamic modulus of elasticity and the relative flexural strength presented clear trends of freeze-thaw resistance of SFRELC. The compound effect of the air-entraining agent and the steel fibers was found to support the SFRELC with high freeze-thaw resistance, and the mechanisms were explored with the aid of the test results of water penetration of SFRELC. The beneficial effect was appeared from the replacement of lightweight sand with manufactured sand. Based on the test results, suggestions are given out for the optimal mix proportion of SFRELC to satisfy the durability requirement of freeze-thaw resistance.